PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN KEPEMILIKAN MANAJERIAL PADA NILAI PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI - Krishna Maheswari, Ni Kadek Jyoti; Adi Erawati, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024, 2024)
The company's goal is to maximize shareholder wealth through maximizing company value. The value of the company provides maximum prosperity for shareholders if the share price increases. So the higher the stock price, the higher the prosperity of the shareholders. This study aims to provide empirical evidence of the effect of firm size, leverage and managerial ownership on firm value in pharmaceutical companies listed on the Indonesia Stock Exchange in 2017-2020. The sample was determined by the non-probability sampling method, purposive sampling technique. The samples obtained were 9 companies with 4 years of observation. The data analysis technique used is multiple linear regression. The results show that firm size has a positive effect, leverage has a negative effect, and managerial ownership has a positive effect on firm value. Companies are expected to pay attention to the financial information presented, especially company size, leverage and dividends as well as non-financial information on managerial ownership in order to provide accurate and relevant information regarding the condition of the company.